Political Education for Young Voters in Facing the 2024 Jambi Provincial Regional Head Elections - Dastina, Wenny; Juharmen; Nuur, Muhammad; Pratama, Irfandi (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
The lack of political literacy among first-time voters poses a significant challenge to improving the quality of democracy, especially ahead of the 2024 Jambi Provincial Head Elections. Low political participation among young voters and high abstention rates underscore the urgency of this community service program. The program aims to deliver structured political education to enhance understanding, awareness, and participation among first-time voters. The method used was Community Service Learning, incorporating workshops, group discussions, election simulations, and pre-test and post-test surveys. The program targeted high school students and university freshmen in Jambi. Results indicated a substantial improvement in participants' political literacy. Knowledge of election schedules increased from 49% to 96.67%, understanding of gubernatorial candidates' visions and missions rose from 43.81% to 96.67%, and awareness of the relationship between elections and democracy improved from 21.43% to 88.10%. This program demonstrates that participatory political education can enhance political literacy and encourage young voters to actively engage in democracy. However, challenges such as political skepticism and low interest in democratic issues require continued efforts. Media literacy and digital platforms are recommended to broaden the program's reach and mitigate the impact of misinformation. In conclusion, sustained political education can foster a more inclusive and participatory democratic culture.